The Impact of Internal Audits on the Effectiveness of Hospital Internal Control Systems - Andri Yulianto; Rita Mardiana (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to analyze the impact of internal audits on the effectiveness of the internal control system in the Nursing Department at the PT KBN Graha Medika General Hospital. Research Method: This study employed a quantitative, associative design. The sample consisted of 111 respondents selected through simple random sampling. Data were collected via an online questionnaire and analyzed using simple linear regression. Results and Discussion: Internal audits have a positive and significant impact on the effectiveness of internal control systems. This suggests that improvements in the quality of internal audit performance are accompanied by greater effectiveness of internal controls. However, their contribution remains limited, indicating that other factors are also at play. Implications: This study makes an empirical contribution by examining the role of internal audits in the operational context of nursing care. This topic has received limited attention in the literature. The findings confirm that internal audits serve as an evaluative mechanism for strengthening internal controls; however, their effectiveness depends on their implementation and support from other organizational factors. Originality: to examine the impact of internal audits on the effectiveness of internal control systems in the context of nursing operations in hospitals.